Menelusuri Jejak Laskar Diponegoro di Pesantren - Rizal Mumazziq Z (STAIFAS-Press, 2016)
Alongside Prince Diponegoro, the scholars work together to fight against Dutch colonialism. They come from various Islamic schools in the kingdom of Mataram. The scholars occupy vital positions in combat units Diponegoro so as to move the people to jihad fi sabilillah against the occupation. After the prince arrested, creed amended struggle with sticking to QS. Attaubah paragraph 122. This strategy change is executed in a characteristic manner; from armed struggle sword, turn to struggle in the field of education, so that one day, this method of birth of thousands of fighters who are not only proficient in a variety of religious knowledge, but also tough on the battlefield independence.Key Word: Warriors of Diponegoro, Pesantren